Spatial distribution of congenital syphilis in the state of Bahia, Brazil from 2009 to 2018 - Vital, Caroline Luz; Reis, Renato Barbosa; Soares, Jorgana Fernanda de Souza; Miranda, Diego Lopes Paim; Reis, Mitermayer Galvão (Frontiers in Epidemiology, 2023)
Objective: To describe the temporal trend and spatial distribution of congenital syphilis (CS) cases in the state of Bahia, Brazil between 2009-2018. Method: Mixed ecological study conducted through the analysis of data obtained from the Notifiable Diseases Information System and the Live Birth Information System. Global Moran Index I was performed in order to analyze spatial autocorrelation of CS cases in the municipalities of Bahia and the Local Spatial Association Indicator (LISA) was used to identify the formation of spatial regimes in the GeoDA software. Results: 8,786 cases of CS were registered in the period. An increasing growth in CS incidence, with a 511% increase between 2009-2018. Spatial autocorrelation was observed between the municipalities (I Moran= 0.452; p <0.001) and four clusters were identified. More frequently, mothers were aged 20-29 years (50.7%); had incomplete primary education (54.9%); were black/brown (93.2%); received prenatal care (82.2%); 49.0% were diagnosed with syphilis during prenatal care; 68.8% were not adequately treated, and 81.1% of their partners were not treated. Conclusion: The results showed that CS consolidates as a serious public health problem in Bahia, with an incidence 8.4 times higher in the period than the WHO target of 0.5/1,000 live births, predominantly related to inadequate prenatal care and social vulnerability 2 This is a provisional file, not the final typeset article indicators: young mothers, with low education levels, brown and black skin. Thus, programs aimed at women of childbearing age and pregnant women need to be intensified.